2012
DOI: 10.1021/nn203519r
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Explants Use Carbon Nanotube Interfaces To Enhance Neurite Outgrowth and To Fortify Synaptic Inputs

Abstract: New developments in nanotechnology are increasingly designed to modulate relevant interactions between nanomaterials and neurons, with the aim of exploiting the physical properties of synthetic materials to tune desired and specific biological processes. Carbon nanotubes have been applied in several areas of nerve tissue engineering to study cell behavior or to instruct the growth and organization of neural networks. Recent reports show that nanotubes can sustain and promote electrical activity in networks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
169
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(180 citation statements)
references
References 58 publications
11
169
0
Order By: Relevance
“…It is therefore suggested that CNTs affect neuronal firing activity and synaptic connectivity in the neuronal layer directly facing CNT scaffold (in agreement with previous findings on dissociated neurons 27,28,30 ), where CNTs intimately and extensively interact with membranes (Figure 4c), 10 and that this alteration is remotely translated into an amplification of synaptic signals at the level of ventral interneurons relatively far from the CNT interface.…”
Section: −3046supporting
confidence: 91%
See 2 more Smart Citations
“…It is therefore suggested that CNTs affect neuronal firing activity and synaptic connectivity in the neuronal layer directly facing CNT scaffold (in agreement with previous findings on dissociated neurons 27,28,30 ), where CNTs intimately and extensively interact with membranes (Figure 4c), 10 and that this alteration is remotely translated into an amplification of synaptic signals at the level of ventral interneurons relatively far from the CNT interface.…”
Section: −3046supporting
confidence: 91%
“…A step beyond these considerations emerged in the same work 10 where we reported, for the first time, the impact of CNT interfaces to cell layers distant from the CNTs themselves. More explicitly, CNT scaffolds are able to modulate the functional performance of neurons spatially far from the scaffold.…”
Section: −3046mentioning
confidence: 88%
See 1 more Smart Citation
“…143 A breakthrough study from Fabbro et al developed for the first time an artificial nanomaterials-based scaffold to explore the semichronic (weeks) impact of CNT interfaces on spinal segment growth and activity. 149 They demonstrated that the long-term impact of an artificial MWNT meshwork characterized by large surface roughness and conductivity 150,151 favors neurite regrowth in spinal explants, with the appearance of increased growth-cone activity (Figure 2). 149 Ultimately, this study supports one of the emerging strategies in nanoscale engineering, which is the use of physical features alone to guide different biological responses, without the levels of sophistication required by biomolecule selective patterning.…”
Section: Cnt and Neuron Interactionmentioning
confidence: 99%
“…149 They demonstrated that the long-term impact of an artificial MWNT meshwork characterized by large surface roughness and conductivity 150,151 favors neurite regrowth in spinal explants, with the appearance of increased growth-cone activity (Figure 2). 149 Ultimately, this study supports one of the emerging strategies in nanoscale engineering, which is the use of physical features alone to guide different biological responses, without the levels of sophistication required by biomolecule selective patterning. 152 CNTs have also been shown to favor the differentiation of human embryonic stem cells (hESCs) into neurons.…”
Section: Cnt and Neuron Interactionmentioning
confidence: 99%